Mechanisms of Progesterone Receptor Inhibition of Inflammatory Responses in Cellular Models of Breast Cancer - Kobayashi, Sakiko (The Endocrine Society, 2010)
Both pro- and antimitogenic activities have been ascribed to progesterone receptor (PR) agonists and antagonists in breast cancer cells; however, the transcriptional responses that underlie these paradoxical functions are not apparent. Using nontransformed, normal human mammary epithelial cells engineered to express PR and standard microarray technology, we defined 2370 genes that were significantly regulated by the PR agonist R5020. Gene ontology (GO) analysis revealed that GO terms involved in inflammation and nuclear factor-κB (NF-κB) signaling were among the most significantly regulated. Interestingly, on those NF-κB responsive genes that were inhibited by agonist-activated PR, antagonists either 1) mimicked the actions of agonists or 2) reversed the inhibitory actions of agonists. This difference in pharmacological response could be attributed to the fact that although agonist- and antagonist-activated PR is recruited to NF-κB-responsive promoters, the physical presence of PR tethered to the promoter of some genes is sufficient for transcriptional inhibition, whereas on others, an agonist-activated PR conformation is required for inhibition of NF-κB signaling. Importantly, the actions of PR on the latter class of genes were reversed by an activation function-2-inhibiting, LXXLL-containing peptide. Consideration of the relative activities of these distinct antiinflammatory pathways in breast cancer may be instructive with respect to the likely therapeutic activity of PR agonists or antagonists in the treatment of breast cancer.